2017
DOI: 10.1161/jaha.117.005945
|View full text |Cite
|
Sign up to set email alerts
|

Alogliptin, a Dipeptidyl Peptidase‐4 Inhibitor, Alleviates Atrial Remodeling and Improves Mitochondrial Function and Biogenesis in Diabetic Rabbits

Abstract: BackgroundThere is increasing evidence implicating atrial mitochondrial dysfunction in the pathogenesis of atrial fibrillation. In this study, we explored whether alogliptin, a dipeptidyl peptidase‐4 inhibitor, can prevent mitochondrial dysfunction and atrial remodeling in a diabetic rabbit model.Methods and ResultsA total of 90 rabbits were randomized into 3 groups as follows: control group (n=30), alloxan‐induced diabetes mellitus group (n=30), and alogliptin‐treated (12.5 mg/kg per day for 8 weeks) diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 49 publications
6
53
1
Order By: Relevance
“…Zhang et al found that DPP-4 inhibitors decreased mitochondrial ROS production rate and ameliorate arrhythmic substrate in a DM rabbit model. 49 In another study, Zou et al illustrated that ranolazine inhibits oxidative stress and improves mitochondrial function in the atrium of acetylcholine-CaCl 2 -induced atrial fibrillation rats partly by increasing the expression of antioxidants such as GSH-Px and manganese superoxide dismutase to reduce ROS levels in mitochondria. 50 Furthermore, in a canine model subjected to atrial tachycardia pacing (ATP, 400 bpm) without atrioventricular block for 4 weeks leading to left ventricular dysfunction, Sakabe et al evaluated the dynamics of atrialtachycardia remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al found that DPP-4 inhibitors decreased mitochondrial ROS production rate and ameliorate arrhythmic substrate in a DM rabbit model. 49 In another study, Zou et al illustrated that ranolazine inhibits oxidative stress and improves mitochondrial function in the atrium of acetylcholine-CaCl 2 -induced atrial fibrillation rats partly by increasing the expression of antioxidants such as GSH-Px and manganese superoxide dismutase to reduce ROS levels in mitochondria. 50 Furthermore, in a canine model subjected to atrial tachycardia pacing (ATP, 400 bpm) without atrioventricular block for 4 weeks leading to left ventricular dysfunction, Sakabe et al evaluated the dynamics of atrialtachycardia remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Allopurinol prevented hyperglycemia‐induced oxidative stress, cardiomyocyte hypertrophy and cardiac fibrosis and attenuated cardiac dysfunction,15 in which prevention of ROS‐induced oxidative stress and reduction of myocardial collagen formation may represent one of the major pathogenic mechanisms. Zhang et al found that DPP‐4 inhibitors decreased mitochondrial ROS production rate and ameliorate arrhythmic substrate in a DM rabbit model 49. In another study, Zou et al illustrated that ranolazine inhibits oxidative stress and improves mitochondrial function in the atrium of acetylcholine‐CaCl 2 –induced atrial fibrillation rats partly by increasing the expression of antioxidants such as GSH‐Px and manganese superoxide dismutase to reduce ROS levels in mitochondria 50.…”
Section: Discussionmentioning
confidence: 99%
“…Block of PAR-1 signaling Oral anti-platelet agent Unknown DPP-4 inhibitors (Lendeckel, 2001;Tremblay, 2014;Wronkowitz, 2014;Gong et al, 2015;Yamamoto, 2015;Chang, 2017;Zhang, 2017;Igarashi, 2018) Sitagliptin, saxagliptin and other gliptins…”
Section: Reduction Of Thrombin Formation (New) Oral Anticoagulantsmentioning
confidence: 99%
“…The International Diabetes Management Practices Study reported that the median body mass index (BMI) of patients with T2D increased from 26 kg/m 2 to 29 kg/m 2 between 2005 and 2017, while the proportion of insulin‐treated patients who achieved the target HbA1c of <7% (53 mmol/mol) decreased from 28% to 16% over the same period, suggesting that achieving the glycaemic target is an additional challenge with increasing BMI. Overweight and obese patients currently form the majority of patients with T2D worldwide, and ~60% of patients with T2D in China have a BMI of ≥25 kg/m 2 , corresponding to ~69 million Chinese adults . However, no specific insulin dosing algorithm has been determined in this population.…”
Section: Introductionmentioning
confidence: 99%